Crystal Structures And Analysis Of 1,2,4 Triazole And Pyrazole Compounds - Goh , Jia Hao (2011)

(untitled)
The purpose of this research is to study the crystal structures of some biologically and pharmacologically important 1,2,4-triazole and pyrazole compounds by single crystal X-ray crystallography method. A series of nine compounds of 1,2,4-triazole derivatives and a series of six compounds of pyrazole derivatives were synthesized and crystallized to obtain single crystals. The data was collected using either Bruker SMART APEXII or Bruker APEXII DUO CCD area-detector diffractometers. The structures were solved by direct methods and refined by least-squares method.